Skin lipids in health and disease. Issue 2 (February 2016) - Nicolaou, A.; Harwood, J. L.
Abstract : Lipids are important for normal skin function. They are generated from two main sources – the epithelial cells and the sebum which is secreted onto the surface. Important functions of the lipids are to contribute to an effective barrier towards water loss, to protect from radiation and to prevent entry of harmful chemicals and microbes. There is also an increasing interest in the inflammatory characteristics of lipid signalling molecules which have important consequences for many common skin complaints. In many cases, these bioactive lipids can be regulated through dietary intervention or by topical and other therapies.